Speech Fluency Improvement in Developmental Stuttering Using Non-invasive Brain Stimulation: Insights From Available Evidence - Busan, Pierpaolo; Moret, Beatrice; Masina, Fabio; Del Ben, Giovanni; Campana, Gianluca (Frontiers in Human Neuroscience, 2021)
Developmental stuttering (DS) is a disturbance of the normal rhythm of speech that may result as very debilitating in the most affected cases. Interventions for DS are historically based on behavioral modifications of speech patterns (e.g. by means of speech therapy), useful to regain a better speech fluency. However, great variability in intervention outcomes is normally observed, and no definitive evidence is currently available to resolve stuttering, especially when it persists in adulthood. In the last decades, DS has been increasingly considered as a functional disturbance, affecting the correct programming of complex motor sequences, such as speech. Compatibly, understanding of the neurophysiological bases of DS has dramatically improved, thanks to neuroimaging, and techniques able to interact with neural tissue functioning (e.g. Non-Invasive Brain Stimulation -NIBS-). In this context, a dysfunctional activity of the cortico-basal-thalamo-cortical networks seems to play a key role, as well as defective patterns of connectivity, especially in sensorimotor networks. As a consequence, acting directly on the functionality of “defective” or “impaired” brain circuits may help people who stutter to better manage dysfluencies. This may also “potentiate” available interventions, thus favoring more stable outcomes of speech fluency. Attempts aiming at modulating (and improving) brain functioning of people who stutter, realized by using NIBS, are quickly increasing. Here, we will review these recent advancements applied to the treatment of DS. Insights will be useful not only to assess whether speech fluency of people who stutter may be ameliorated acting directly on brain functioning, but they will also provide further suggestions about the complex and dynamic pathophysiology of DS, where causal effects and “adaptive”/”maladaptive” mechanisms of compensation may be strongly overlapping. In conclusion, this review focuses future research toward more specific, targeted, and effective interventions for DS, based on neuromodulation of brain functioning.